1994
DOI: 10.1104/pp.105.4.1439
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Sequence for the Plastidic Phosphoglucomutase from Spinacia oleracea (L.)

Abstract: , for providing the yeast mutant strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…These experiments revealed that St pPGM was imported into the plastid and that the transit peptide was cleaved resulting in the formation of a 62 kDa mature peptide. The sequence homology of St pPGM cDNA in comparison to that from Spinacea oleracea is only 19%, which is surprisingly low ( Penger et al . 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments revealed that St pPGM was imported into the plastid and that the transit peptide was cleaved resulting in the formation of a 62 kDa mature peptide. The sequence homology of St pPGM cDNA in comparison to that from Spinacea oleracea is only 19%, which is surprisingly low ( Penger et al . 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps consistent with the hypothesis that plastids are derived from ancient prokaryote symbionts. A spinach PGM sequence reported by Penger et al (1994) does not show a high degree of homology to any of the identified plant PGMs. With the sequence data now available from numerous plant species, it seems highly unlikely that this clone was a PGM.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA species of 4 kb may be assigned to the yeast DNA fragment detected by Boles et al (1994) containing short dispersed similarities to yeast PGM genes. PGM was sequenced in a variety of cell types including bacteria (Lu and Kleckner 1994;Qian et al 1994), plant (Penger et al 1994) and mammals (Ray et al 1983;Whitehouse et al 1992;Rivera et al 1993;Lee at al. 1992) with three genes and several isoforms found in humans (Edwards et al 1995).…”
Section: Discussionmentioning
confidence: 99%